ETHNOMEDICINAL SURVEY OF MEYNA LAXIFLORA IN TRIBES OF AKKALKUWA, NANDURBAR DISTRICT - QUAZI MAJAZ A.,; MOLVI KHURSHID I, (International Journal of Pharma and Bio Sciences, 2014)
Plants have been used both in the prevention and cure of various diseases of humans and their pets. With the beginning of human culture, different medicinal systems have been developed comprising on plants. It is estimated that there are 250,000 to 500,000 species of plants on Earth. Relatively small percentages (1 to 10%) of these are used as foods by both humans and other animal species. It is possible that even more are used for medicinal purposes. Meyna laxiflora is a plant which having traditional importance for its medical uses, for treatment of Inflammation, Gastrointestinal disorder etc. It is distributed all over the satpuda region in Nandurbar district it is found in Sawarimal, Umarpata, Morkaranja and kondaibari. But lacking in information about an ethnomedicnal uses of this plant from tribes of satpuda region, hence it is necessary to initiate ethnomedicinal survey of this plant in Nandurbar District.